4/(z+2)-1/(3z+6)=11/9

Simple and best practice solution for 4/(z+2)-1/(3z+6)=11/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/(z+2)-1/(3z+6)=11/9 equation:


D( z )

3*z+6 = 0

z+2 = 0

3*z+6 = 0

3*z+6 = 0

3*z+6 = 0 // - 6

3*z = -6 // : 3

z = -6/3

z = -2

z+2 = 0

z+2 = 0

z+2 = 0 // - 2

z = -2

z in (-oo:-2) U (-2:+oo)

4/(z+2)-(1/(3*z+6)) = 11/9 // - 11/9

4/(z+2)-(1/(3*z+6))-(11/9) = 0

4/(z+2)-(3*z+6)^-1-11/9 = 0

4/(z+2)-1/(3*z+6)-11/9 = 0

(4*9*(3*z+6))/(9*(z+2)*(3*z+6))+(-1*9*(z+2))/(9*(z+2)*(3*z+6))+(-11*(z+2)*(3*z+6))/(9*(z+2)*(3*z+6)) = 0

4*9*(3*z+6)-1*9*(z+2)-11*(z+2)*(3*z+6) = 0

99*z-33*z^2-132*z-132+198 = 0

66-33*z^2-33*z = 0

66-33*z^2-33*z = 0

33*(2-z^2-z) = 0

2-z^2-z = 0

DELTA = (-1)^2-(-1*2*4)

DELTA = 9

DELTA > 0

z = (9^(1/2)+1)/(-1*2) or z = (1-9^(1/2))/(-1*2)

z = -2 or z = 1

33*(z+2)*(z-1) = 0

(33*(z+2)*(z-1))/(9*(z+2)*(3*z+6)) = 0

(33*(z+2)*(z-1))/(9*(z+2)*(3*z+6)) = 0 // * 9*(z+2)*(3*z+6)

33*(z+2)*(z-1) = 0

( z+2 )

z+2 = 0 // - 2

z = -2

( z-1 )

z-1 = 0 // + 1

z = 1

z in { -2}

z = 1

See similar equations:

| y^4+y^3+2y^2=0 | | 6x+2=5x+6 | | 2x-3/6+3x-2/4+5x+6/12=4 | | 75=3(10t-3)6t | | 2+5x=7+4x | | -x-4=-2x | | -18(13y+12)=-17+16(13y+8)-15(9y+17) | | 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x | | -14+28x+26x=16x-12+8x | | -14-28x+26x=16x-12+8x | | 91=7(1+2x) | | 2x+4=39-5x | | 24z+27+13z=25-9z-5z | | 3=16+(x+1) | | -x+4=-2x+6 | | 9-4y=-11-6y | | -3x+4=-4x+9 |

Equations solver categories